2006
DOI: 10.1007/s10495-006-4030-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of elongation factor 2 on apoptosis induced by HIV-1 viral protein R

Abstract: Rapid CD4+ lymphocyte depletion due to cell death caused by HIV infection is one of the hallmarks of acquired immunodeficiency syndrome. HIV-1 viral protein R (Vpr) induces apoptosis and is believed to contribute to CD4+ lymphocyte depletion. Thus, identification of cellular factors that potentially counteract this detrimental viral effect will not only help us to understand the molecular action of Vpr but also to design future antiviral therapies. In this report, we describe identification of elongation facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
(52 reference statements)
3
36
0
Order By: Relevance
“…However, results of this report on mdr PRs and our earlier study on the wt PR [32] suggested that mdr PR-induced cell death in fission yeast was reminiscent of PR-induced apoptosis in mammalian cells [29, 40]. This was evident by the fact that HIV-1 mdr PRs not only triggered the ROS production but also caused mitochondrial changes that were linked to apoptosis [29, 41].…”
Section: Discussionmentioning
confidence: 85%
“…However, results of this report on mdr PRs and our earlier study on the wt PR [32] suggested that mdr PR-induced cell death in fission yeast was reminiscent of PR-induced apoptosis in mammalian cells [29, 40]. This was evident by the fact that HIV-1 mdr PRs not only triggered the ROS production but also caused mitochondrial changes that were linked to apoptosis [29, 41].…”
Section: Discussionmentioning
confidence: 85%
“…Consistent with this model, inactivating eEF-2 in other ways, such as doxorubicin-induced phosphorylation 55 or diphtheria toxin-mediated ADP ribosylation 56,57 of eEF-2, also causes cell death, whereas potentiating eEF-2 activity can protect cells from some apoptotic stimuli. 58 Therefore, eEF-2K may promote cell death during ER stress via its effect on translation elongation. With respect to the mechanistic models of eEF-2 phosphorylation induction, our results show that, in contrast to sal (discussed below), Tm induces eEF-2 phosphorylation in eIF2a A/A MEFs (Figure 4a) but not in eEF-2K À/À MEFs (Figure 3b), demonstrating that eEF-2K is necessary for this signaling event during ER stress but eIF2a phosphorylation is not.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the strain that displays the highest intracellular ROS production had the lowest sensitivity towards H 2 O 2 treatment. In this context it is interesting to note that upon expression of the HIV protein Vpr in S. pombe (which, as mentioned before, causes apoptosis-like cell death) the intracellular levels of both complementing proteins hsp16 [13] and Ef2 [14] were observed to be elevated, which indicates dynamic interplay between the expression of foreign pro-apoptotic genes and endogenous anti-apoptotic responses. Similarly, an increase in the activity of endogenous ROS-defense mechanisms might be responsible for our observation that mitochondrial ROS production does not cause a significant drop in survival rates.…”
Section: Resultsmentioning
confidence: 67%
“…In this way, overexpression of fission yeast hsp16 was shown to specifically suppress Vpr induced cell death by a heat shock factor Hsf1-dependent mechanism [12,13]. Another group recently identified fission yeast elongation factor 2 (Ef2) through a genomewide search for multicopy suppressors of Vpr-induced cell death and subsequently demonstrated that overexpression of its human homologue also blocks Vpr-induced apoptosis in several mammalian cell lines [14]. As far as we know today, some mechanisms of programmed cell death are conserved between fission yeast and mammals while others are not, and we are just starting to learn for which aspects of apoptosis S. pombe can serve as a useful model.…”
Section: Introductionmentioning
confidence: 99%